El esqueleto de la viuda Houet: Frenología y medicina legal en Francia durante la década de 1830 - José Ramón Bertomeu-Sánchez (Criminocorpus)
This paper deals with the judicial identification of corpses in nineteenth-century France. The case of the widow Houet (1833) is particularly interesting for this purpose because two contrasting techniques of identification were employed: forensic medicine and phrenology. Mateu Orfila, dean of the Paris Faculty of Medicine, had recently developed a quantitative method for the identification of corpses, which was later regarded as a landmark in nineteenth-century forensic medicine. Pierre-Marie Dumoutier, an outstanding member of the Society of Phrenology, analysed the skull and offered surprising data about the personality of the widow. The episode stirred up controversies on the evidentiary value of phrenology and medicine in criminal investigations. Thanks to these controversies, I discuss three different points: the implicit rules of admissibility of expert knowledge in nineteenth-century French courts; the politics of legal medicine and phrenology regarding crime, penal system and prisons; and the tensions and unequal exchanges between legal medicine and phrenology in terms of people, data, objects, spaces and practices.